Escrever para si, escrever sobre si: a literatura lésbica entre o virtual e o impresso - Holanda, Ismênia de Oliveira (2015)
This Master's thesis analyzes the trajectory of Karina Dias, an openly lesbian writer who before published only in blogs and facing sites lesbian culture and now also publishes in printed books. This writer talk openly about homosexuality, writes texts aimed at lesbians and whose main characters also appear that socio-sexual micro- universe. The internet was a key route of this research, as we study the formation of Brazilian writers having as driving element of their careers the advent of blogs and disclosure of lesbians texts sites. It has been the objective from the examination of this particular trajectory, understand the process of transition of the digital world writers for printed, as well as their relationship with these two types of publication (virtual and physical), these publications that cannot more be separated on the importance of the Internet as a means of dissemination of new writers and new works. We conducted a study of the works of this writer and, more deeply, analyzed the trajectory of her life, in order to describe points of continuity and discontinuity in the experience of being a writer belonging to a sexual minority, and that's turned to writing this minority.